2010
DOI: 10.1123/tsp.24.1.97
|View full text |Cite
|
Sign up to set email alerts
|

A Framework to Explore and Transform Client-Generated Metaphors in Applied Sport Psychology

Abstract: Metaphors are pervasive in everyday language, thoughts and actions (Lakoff & Johnson, 1980). The field of sport psychology, and more explicitly practitioner-client dialogue, remain exposed to such communication. Despite the prevalence of metaphor in our daily interactions, metaphorical discourse is often ignored, or unknowingly used in therapeutic settings (Jinks, 2006). However, noticing a client’s use of metaphor may provide an opportunity to work within the athlete’s metaphorical landscape (i.e., the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…These forms of expression represent unfamiliar terrains for sport injury and offer exciting avenues for future professional practice research (cf. Lindsay, Thomas, & Douglas, 2010). After hearing injured athletes' stories, the SPCs highlighted the importance of having a detailed understanding of personal and situational factors that can help to inform subsequent action (i.e., Contextualize the Story).…”
Section: Discussionmentioning
confidence: 99%
“…These forms of expression represent unfamiliar terrains for sport injury and offer exciting avenues for future professional practice research (cf. Lindsay, Thomas, & Douglas, 2010). After hearing injured athletes' stories, the SPCs highlighted the importance of having a detailed understanding of personal and situational factors that can help to inform subsequent action (i.e., Contextualize the Story).…”
Section: Discussionmentioning
confidence: 99%
“…that controlling or eliminating internal events may provide temporary relief in the short term, yet have noticeable costs in the long term by preventing valued action). The use of metaphors may also be effective due to being memorable and tangible (Anderson, Lau, Segal & Bishop, 2007;Lindsay, Thomas & Douglas, 2010)indeed, Mel indicated that they were 'easy to grasp' (perhaps a relevant consideration given her age; Knight, Harwood & Gould, 2018).…”
Section: Interventionmentioning
confidence: 99%
“…Lindsay, P., Thomas, O., & Douglas, G. (2010). Exploring and transforming client generated metaphors in applied sport psychology.…”
Section: Publicationmentioning
confidence: 99%
“…This contrast should be encouraged if the discipline is to continue to meet the evolving demands of elite sport. Identifying such approaches (e.g., Lindsay, et al, 2010; may serve to move both the discipline and the practitioner forward, into a more impactful and effective state of affairs.…”
Section: Viamentioning
confidence: 99%